Dinamika Temporal Pertumbuhan Delta dan Perubahan Garis Pantai di Muara Sungai Blorong, Kendal, Jawa Tengah, Indonesia (1972-2024) - Rio Daffa Alfani; Aga Rizky (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Coastal zones are dynamic transitional environments subject to continuous morphological change driven by fluvial, marine, and anthropogenic processes. This study investigates the temporal dynamics of delta growth and shoreline change at the Blorong River estuary, Kendal, Central Java, Indonesia, over 52 years (1972 to 2024) using multi-temporal remote sensing analysis based on Landsat imagery series 1 to 8 processed in ArcGIS. The results show a total delta accretion of 2.5852 km² with an average rate of 0.0549 km²/year. The accretion occurred in four distinct phases, namely 0.0714 km²/year during 1972 to 1988, 0.0952 km²/year during 1988 to 1999, 0.0393 km²/year during 1999 to 2009, and 0.0138 km²/year during 2009 to 2024. The progressively declining growth rate suggests a reduction in delta progradation intensity over time, reflecting the combined influence of decreasing upstream sediment supply, dam construction, land-use change, groundwater extraction-induced subsidence, and sea-level rise. These findings highlight the need for integrated coastal zone management through watershed-scale sediment budgeting, mangrove-based coastal protection, and periodic remote sensing monitoring. Future research should incorporate sediment flux measurements, InSAR-based subsidence analysis, and hydrodynamic modeling to improve the understanding of delta evolution and vulnerability under changing climate conditions.